ANALISIS RASIO PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - ", Nurbaiti; Farida, Lena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Financial level assessment of a company can be done by analyzing the company's financial statements . to determine whether the company's financial condition in the condition that baikdapat performed with various analyzes , one of which is a ratio analysis.purpose of this study was to determine the financial performance of the bank bumn the period 2010-2014 in the review of the profitability ratio analysis . the method used is descriptive analysis using a measurement of profitability ratios of return on assets , return on equity , net interest margin and operating expenses . Data and information were obtained from branches pekanbaru Indonesia stock exchange located on the street generals sudirman no, 73.From the results of data analysis using ratio analysis profitability can be concluded that the ratio of Return on Assets , Return on Equity and Net interst margin on state-owned bank has fluctuated and as a whole can be categorized as good , while operational costs in state-owned banks has fluctuated for each bank and in the category of bad .Keywords : analysis , profitability ratios , financial performance